AN ANNOTATED TRANSLATION OF ENGLISH BOOK - Yuliyanti, Yuliyanti (Universitas Gunadarma, 2019)
This research is an annotated translation. This research uses introspective and retrospective method. The researcher collected 100 data to be translated into the writer’s language that is Indonesian language. Of 100 data translated, 30 data were difficult ones to be translated by the researcher. To solve the problems encountered by the researcher, the researcher uses some translation strategies, translation principles, and translation theories. The translation theory used by the researcher is Larson’s theories, consisting four areas namely problem of lexicon, problem of grammatical structure, problem of communication situation and problem of cultural context. Meanwhile, the strategy used by the researcher is Chesterman’s strategy, namely loan, calque, synonym, explicitness change, descriptive, phrase structure change, naturalization, cultural filtering etc. The translation principle used by the researcher is Duff’s principle. Some other theories are also used in this research such as from Nida and Taber, Newmark, Duff, Mona Baker, etc.